1999
DOI: 10.1038/sj.jea.7500059
|View full text |Cite
|
Sign up to set email alerts
|

Estimating environmental exposures to sulfur dioxide from multiple industrial sources for a case–control study

Abstract: This paper first discusses how population exposures to environmental pollutants are estimated from environmental monitoring data and the problems that are encountered in estimating risk from pollutants on the basis of ecologic studies. We then present a technique of estimating individualized exposures to an atmospheric pollutant, sulfur dioxide ( SO 2 ) , through atmospheric transport modeling for a case ± control study. The transport model uses the quantities of SO 2 released from 30 geographically identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As with other exposure estimators, dispersion modeling is also subject to uncertainty (Sexton et al, 1992 ). Uncertainty in dispersion modeling results was evaluated in a recent study estimating SO 2 levels resulting from emissions from multiple industrial facilities in southeastern Georgia, USA (Rogers et al, 1999 ) . Rogers et al conducted transport model uncertainty analysis and found very little difference in monitored versus modeled pollutant levels when using effective stack height in dispersion modeling.…”
Section: Discussionmentioning
confidence: 99%
“…As with other exposure estimators, dispersion modeling is also subject to uncertainty (Sexton et al, 1992 ). Uncertainty in dispersion modeling results was evaluated in a recent study estimating SO 2 levels resulting from emissions from multiple industrial facilities in southeastern Georgia, USA (Rogers et al, 1999 ) . Rogers et al conducted transport model uncertainty analysis and found very little difference in monitored versus modeled pollutant levels when using effective stack height in dispersion modeling.…”
Section: Discussionmentioning
confidence: 99%
“…This classification is analogous to that carried out in Section III by using the Wilcoxon rank sum test for the medians. With the estimators (T (0.2), s W (0.2)) and (T bi (9), s bi (9)), the classification of the variables is equivalent to that obtained by using nonparametric estimators. However, the difference is that X 10 can form a category by itself in the groupings given by the pair of estimators (T (0.2), s W (0.2)).…”
Section: A Central Tendency and Scale Estimatorsmentioning
confidence: 99%
“…In [9], a method of estimating exposure to SO 2 was presented. The Gaussian plume atmospheric transport model used in [9] was introduced by [10] and [11], and it obtained the average ground-level concentration of SO 2 over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations